Dinamika Komunikasi Kelompok Antar Rumpun Keluarga dalam Upacara Adat Perkawinan di Desa Wuasa Kecamatan Lore Utara, Kabupaten Poso - Mendi, Agung (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
Implementation of traditional wedding ceremonies in North Lore District has diversity in its implementation according to the traditions of the community or the customs of each village where the traditional wedding ceremony will be held and also based on the results of the family agreement. This research is based on a qualitative approach to the descriptive method of the concept which aims to provide a systematic description and analyze the object under study. The subjects of this research are family members who want to carry out marriage activities in Wuasa village. There were six (6) informants in this study. The data collection techniques used are observation, in-depth interviews and documentation. The results of this study indicate that in the process of traditional marriages in Wuasa village, the dynamics of group communication between family groups can be seen from the frequency with which family groups and traditional institutions gather to discuss violations before marriage and how to carry out marriages.